A hybrid cellular automata-finite element model for the simulation of the grind-hardening process - Salonitis, Konstantinos (Springer, 2017)
Grind-hardening process is a hybrid process for the simultaneous finishing and heat treatment of the workpiece material. Several studies have been presented for the simulation of the process, using either analytical or finite element-based models. In the present paper, the cellular automata method is used for simulating the metallurgical changes in the workpiece material. The method is coupled with a finite element model for the macro-modelling of the process, allowing the prediction of the microstructure of the material as a function of the macro-process parameters.
Keywords: Grinding Modelling; Surface hardening; Cellular automata